Noise Mapping and Assessment of the Acoustic Environment in Coastal Puducherry, an Old French City: A Cross-Sectional Study - Venkatesan, Dr. Vijayabaskar; Gupta, Dr. Richa; Singh, Dr. Nikhilesh; ArunTipandjan, Dr.; SaravananAyyavoo, Dr.; S, Dr Krishnan (International Journal of Aquatic Research and Environmental Studies, 2026)
Introduction: According to the Central Pollution Control Board (CPCB) National Ambient Noise Monitoring Network data (2019), about 90 % of monitoring stations in major Indian cities recorded noise levels above the accepted limits, both during day and night. Urban environments like Puducherry exhibit complex spatial and temporal variations in noise pollution due to diverse land use patterns, dense traffic networks, and mixed residential-commercial zones. Aim: This study aims to enhance ambient noise mapping across Puducherry’s through the geospatial analysis techniques to identify the hot spots in Urban area of Puducherry. Methods and Materials: Cross-sectional research was undertaken in October 2023 in Puducherry’s urban areas. The grid size was established by the physics rule, which stipulates that increased vehicle traffic causes higher levels of noise. Spatial analysis was conducted at preliminary 2-hour static monitoring at three suspected noise sources, Coefficient of variation CV<0.5, successfully predicting high-variability in urban signals across 42 GPS points measuring 5-minute Leq. A systematic selection of 9 places was chosen by spatial analysis from 42 spots in Urban area. The sound level was measured with Larson Davis Sound Expert LxT meters and calibrated as pre measurement according to CPCB/ISO 1996-2 guidelines. Results: Our results reported an increase in the Indhira Gandhi Square signal (Leq dB – 103.5), Maraimalai Adigal Salai near the bus stand to Nellitope (Leq dB(A) - 96.9), Vazhudavoour Road near Rajiv Gandhi Square (94.1), Saram signal, Kamaraj Salai, Lenin Street (93.1), and Anna Salai bus stand (90.8) of study sites from afternoon to evening measurements. Lmin and Lmax vary from 52 to 84 dB and 101 to 113 dB. Conclusion: The noise measurement given in this study reported that in urban Puducherry, vehicle traffic noise surpassed the CPCB’s daytime ambient air quality standard in 90% of the studied areas.